PENGEMBANGAN MODEL PEMBELAJARAN IPA BERBASIS PERMAINAN TRADISIONAL TENGGE-TENGGE KELAS V di SD - Silvianingsih Abdulrahman; Gamar Abdullah; Isnanto (JAMBURA Elementary Education Journal, 2022)
The research was a Research and Development. The development design was done based on a 4-D device development model development by Thiagarajan, which comprised stages of define , design, development, and disseminate. Problem statements of this research were 1) how the real condition of the implementation of Natural Science learning at Elementary School was, 2) how conceptual model of tengge-tengge traditional game-based Natural Science learning model at Elementary School that was development, and 3) how the validity of the conseptual model of tengge-tengge traditional game-based Natural Science learning model at Elementary School was. The method to collect data used observation, documentation, interview, and product assessment. The subjects in this research were 26 students at grade V of SDN 6 Kabila, while the samples were 26 students. The finding of the research was a conceptual model of tengge-tengge traditional game-based Natural Science learning model at grade V of Elementary School in Bone Bolango District. The product created in this research was a guideline of conceptual model of Natural Science learning model with following result of validation obtained percentage of 97,72 % or 98%, and practitioner expert validation obtained percentage of 100% with the average score for validation result of 97% with “very valid” criteria.